PERBANDINGAN KUALITAS LAYANAN TERHADAP LOYALITAS PASIEN KUNJUNGAN LANGSUNG DENGAN PASIEN YANG MENGGUNAKAN TELEMEDICINE DI DKI JAKARTA - Syifa Faradhilah Putri (2023)
Telemedicine can increase the effectiveness and efficiency of healthcare. However, there's still a gaps in patient experience between direct visit and telemedicine. In the midst of fierce competition, companies must be able to retain customer loyalty. Loyalty is positively influenced through satisfaction and the ability of services providers to satisfy the customer.This research was conducted in DKI Jakarta using quantitative research method with cross sectional approach. Data analysis was using path analysis method and dependent t test. The result of this study are service quality has significant effect on both patient satisfaction who directly visits healthcare and using telemedicine. Service quality also has a significant effect on patient loyalty for directly visits healthcare but has no significant effect on patient who use telemedicine. Satisfacation has a significant effect on both patient loyalty for direct visits and those using telemedicine.Meanwhile service quality through satisfaction has a significant effect on patient loyalty using telemedicine and has no effect on directly visits patient. Besides that, there's a significant difference between service quality and patient satisfaction of directly visits pastient and those who use telemedicine, but there's no difference in patient loyalty who directly visits healthcare and those who use telemedicine.